Thermoelectric installation for lifting objects from shallow reservoirs using the freezing method - O. V. Evdulov; D. V. Evdulov; I. A. Gabitov; M. U. Yakhyaev (Вестник Дагестанского государственного технического университета: Технические науки, 2024)
Objective. The purpose of the study is to develop the design of a thermoelectric installation for lifting objects from shallow reservoirs using the freezing method, as well as its calculation, analysis of parameters and electrical and thermophysical characteristics. Method. The research is based on the use of methods of thermodynamic analysis, full-scale and computational modeling of cryogenic equipment in order to find optimal solutions for the reliability and service life of low-temperature installations. Result. The installation includes a waterproof probe, on the end surface of which, facing the bottom of the reservoir, thermoelectric modules are installed, heat is removed from the hot junctions of which by means of a heat removal system made in the form of an all-metal heat pipe or in the form of a thermal thermosiphon. The connection between the object lifted from the reservoir and the thermoelectric installation is carried out through a cold wall by freezing. The thermoelectric installation was calculated and its parameters were determined. Graphs were constructed and dependencies were obtained describing the main characteristics of TEMs included in the thermoelectric installation. The graphs are presented at a temperature of the hot junctions of the TEM of 300 K and the achievement of such values of the thickness of frozen water ice on the cold wall of the technical device that would allow lifting objects from a reservoir up to 4 m deep. Conclusion. The installation parameters have been determined: the number of TEMs of the DRIFT-1.2 type is 8, the operating power range of a single TEM of the DRIFT-1.2 type is from 14 to 40 W with an average temperature difference between the junctions of 45 K, the supply current is from 3.8 to 7 .6 A with power consumption from 50 to 200 W, coefficient of performance - from 0.1 to 0.45, minimum temperature of the cold wall of the TU - 248 K, a domestically produced thermal thermosyphon is used as a heat removal system from the hot junctions of the TEM.